Physiochemical and rheological characteristics of sorbitol based low sugar cherry jam - Bakshi, Rayees Ahmad; khanday, Shazia; Khan, Zakir S; Dar , B N (Journal of Postharvest Technology, 2020)
Production of low – sugar cherry jam was investigated by substituting sucrose with sorbitol in different ratios. The treatments were 101 (100% sucrose), 102 (100% sorbitol), 103 (75% sorbitol), 104 (50% sorbitol) and 105 (25% sorbitol). All the five treatments were examined for physicochemical properties, sensory properties and rheological properties. The TSS and pH observed were in the range of 66.43-66.46°B and 3.3.49-3.51 respectively in different treatments while as acidity calculated in these treatments were maximum in sample 102 and minimum in101. Color parameters showed that lightness and yellowness increases in the range of 22-36 and 31-37 while as redness decreases in the range of 18-14. Rheological properties of cherry jam were evaluated by using rheometer that showed the G′ value is higher than G″ value which indicates that the jam with different sorbitol concentrations shows more elastic behavior. However, viscosity decreases with increase in shear rate. Also, organoleptic characteristics like (Flavour, taste, texture, color and appearance) were examined by trained panellist using 9- points Hedonic Scale. It was observed that the organoleptic score of the sample 103 was the highes